2016
DOI: 10.1038/srep36396
|View full text |Cite
|
Sign up to set email alerts
|

H2O2 and Ca2+-based signaling and associated ion accumulation, antioxidant systems and secondary metabolism orchestrate the response to NaCl stress in perennial ryegrass

Abstract: Little is known about the interplay between Ca2+ and H2O2 signaling in stressed cool-season turfgrass. To understand better how Ca2+ and H2O2 signals are integrated to enhance grass acclimation to stress conditions, we analyzed the rearrangements of endogenous ion accumulation, antioxidant systems and secondary metabolism in roots, stems and leaves of perennial ryegrass (Lolium perenne L.) treated with exogenous Ca2+ and H2O2 under salinity. Ca2+ signaling remarkably enhanced the physiological response to salt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…Redox hemostasis and signalling play a role in response to abiotic stressors such as drought, low temperature and osmotic stress (Hu, Chen, Hu, Amombo, & Fu, ; Liu et al, ; Munemasa et al, ). SlRBOH1 is a homologue of Arabidopsis RBOHF , and it has the highest transcript abundance within the RBOH family in tomato (Zhou et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Redox hemostasis and signalling play a role in response to abiotic stressors such as drought, low temperature and osmotic stress (Hu, Chen, Hu, Amombo, & Fu, ; Liu et al, ; Munemasa et al, ). SlRBOH1 is a homologue of Arabidopsis RBOHF , and it has the highest transcript abundance within the RBOH family in tomato (Zhou et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been found that mycorrhizal fungi exhibit a tolerance in context to abiotic stresses like chilling, drought, salinity, heavy metal exposure and temperature in pea, rice, sunflower and tomato crops (Grover et al ). In addition to that, several studies highlighted the role of cell signaling involving secondary messengers like abscisic acid (ABA), calcium (Ca 2+ ), H 2 S and nitric oxide (NO; Hu et al , Kollist et al , Waidyarathne and Samarasinghe ). Thus, now researchers have started studying these secondary messengers and their role in cell signaling.…”
Section: Biosynthesis Of H2s and No In Plant Cellsmentioning
confidence: 99%
“…P2Y2 receptor activation by ATP stimulation is essential for mechanical stress‐activated calcium influx (MSACI) (Katz, Boland, & Santillan, ). Ca 2+ signaling sustain ROS homeostasis (Hu, Chen, Hu, Amombo, & Fu, ). ROS generation promotes Ca 2+ influx (Yao et al, ).…”
Section: Pannexin Hemichannels Have An Intimate Connection With Oxidamentioning
confidence: 99%